(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2023)
The current research deals with the topic (family solidarity and sustainability), a case study of the UAE, as one of the axes of social development, important in facing social and economic problems facing families, thus directly affecting the factors of sustainability of family stability. The research aims to reveal the most prominent procedures, policies, and initiatives undertaken by the UAE in supporting families, and to identify its role in supporting family solidarity in its relationship to sustainability and sustainable development in international standards, especially related to the achievement of economic and social sufficiency of the families, and to confirm its role in supporting the cohesion of families, and the sustainability of their stability. The research was based on the descriptive-analytical method. To fit it with the nature of the subject studied, and relied on collecting information and analysing its content, reviewing the content of data, policy documents, and procedures that the UAE has implemented in the field of family care, and its approach to the concept of family solidarity, sustainability, and sustainable development goals, according to the Global Agenda 2030AD, in addition to a number of relevant statistical indicators. The research shows that the UAE has undertaken many initiatives and measures, and launched a number of policies that work to support family cohesion and enhance elements of solidarity among its members. It showed the integration of these procedures and policies with other dimensions of development, economy, and environment, and their compatibility with the sustainable development goals known as the “2030 Agenda”, the research revealed the existence of gaps that reduce family solidarity and negatively affect family cohesion, such as high divorce rates, and late age of marriage for women, and recommended a number of measures to avoid these gaps, which reflects positively on development, thus ensuring its sustainability.